Enhancing immunization during second year of life by reducing missed opportunities for vaccinations in 46 countries. Issue 23 (31st May 2018) - Hanson, Celina M.; Mirza, Imran; Kumapley, Richard; Ogbuanu, Ikechukwu; Kezaala, Robert; Nandy, Robin
Abstract: Background: Delivering vaccination services during the second year of life (2YL) 1 provides countries with an opportunity to achieve greater coverage, to provide booster doses and vaccines missed during the first year of life, as well as contribute towards disease control and elimination goals. Methods: Using data from demographic health surveys (DHSs) conducted during 2010 to 2016, this paper explores the proportion of missed opportunities for vaccinations generally provided during routine immunization among children in their 2YL. Results: DHS data in 46 countries surveyed 478, 737 children, from which 169, 259 children were 12–23 months old and had vaccination/health cards viewed by surveyors. From this group, 69, 489 children aged 12–23 months had contact with health services in their 2YL. Three scenarios for a missed opportunity for vaccinations were analysed: (1) a child received one vaccine in the immunization schedule and was eligible for another vaccine, but did not receive any further vaccination, (2) a child received a vitamin A supplementation (VAS) and was due for a vaccine, but did not receive vaccines that were due, and (3) a child was taken to a health facility for a sick visit and was due (and eligible) for a vaccine, but did not receive the vaccine. A total of 16, 409 (24%) children had one or more missed opportunities for vaccinations. Conclusion: This analysis highlights the magnitude of the problem of missed opportunities in the 2YL. The global community needs to provide better streamlined guidance, policies and strategies to promote vaccination screenings at well-child and sick child visits in the 2YL. Where they do not exist, well-child visits in the 2YL should be established and strengthened.